New species of Eublaberus Hebard, 1920, new records for the genus and description of the male of E. variegatus R. S. Albuquerque, 1972 (Blaberidae, Blaberinae) - Lopes, Sonia Maria; Oliveira, Edivar Heeren de; Khouri, Andrea (Biota Neotropica, 2015)
A new species of Eublaberus (E. serranus sp. nov), also a new record for the genus in Southern Brazil, is described based on the male genitalia. The name Eublaberus variegata is corrected to Eublaberus variegatus Rocha e Silva Albuquerque, and the male of the species is described. Illustrations of the genitalia of the two species mentioned are presented and a key to species is also given.